2018
DOI: 10.31768/2312-8852.2018.40(1):10-18
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL IMPLICATIONS OF p53 ALTERATIONS IN ORAL CANCER PROGRESSION: A REVIEW FROM INDIA

Abstract: p53 plays a central role in prevention of normal cell from the development of the malignant phenotype. Somatic alterations (mutations, loss of heterozygosity, deletions) in p53 are a hallmark of most human cancers and cause defects in normal p53 function. However, in the tumors harboring wild-type p53, there are alterations in the regulation of the p53. Thus, understanding why p53 is unable to perform its role as a tumor suppressor in these wild-type tumors is very crucial. Germ-line polymorphisms in p53 are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…P53 has an important role in preventing the formation of malignant cells from normal cells. In a study by Patel et al [54], destruction of p53 by E6 in high-risk HPVs was considered as a possible mechanism for the observed low level of p53 in oral cancers. Similarly, Walline and Pinatti showed that viral integration with micro-RNAs alter the expression of regulatory molecules and may facilitate oncogenesis [55].…”
Section: Discussionmentioning
confidence: 99%
“…P53 has an important role in preventing the formation of malignant cells from normal cells. In a study by Patel et al [54], destruction of p53 by E6 in high-risk HPVs was considered as a possible mechanism for the observed low level of p53 in oral cancers. Similarly, Walline and Pinatti showed that viral integration with micro-RNAs alter the expression of regulatory molecules and may facilitate oncogenesis [55].…”
Section: Discussionmentioning
confidence: 99%
“…The latter binds and promotes the degradation of the TP53 tumor suppressor gene product [7]. This gene is widely used in the study of cancers as it is commonly mutated in human cancers and in about 50% of malignant tumors [1,8]. Several mechanisms lead to the alteration of the P53 protein response, but somatic mutations in the gene are one of the most universal mechanisms during oral carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Its prognostic value in OCC has long been debated. Conflicting results have been published on the presence or absence of mutations in this gene, with variations in their frequencies across OCCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of cancers in humans express a mutation in this gene [3][4][5]. The encoded protein mediates in the prevention of neoplastic transformation by repairing DNA damages after replication, or by inducing apoptosis in case DNA damages couldn't be repaired [6].…”
Section: Introductionmentioning
confidence: 99%